Produção de carvão ativado sulfonado a partir do bagaço de cana-de-açúcar para conversão de glicose e celobiose à hidroximentilfurfural - Silva, Ludimila Marques (2023)
The importance of new heterogeneous catalyst techniques to obtain furanic compounds is fundamental in the search for renewable sources of energy and sustainable chemical products. The synthesis of C6 sugars from lignocellulosic biomass has aroused considerable interest in the scientific community, due to the ability of these compounds to serve as platform molecules to obtain a variety of chemical substitutes for fossil derivatives. In this context, the feasibility of producing hydroxymethylfurfural (HMF) through the dehydration of cellobiose and glucose using heterogeneous catalysts based on sulfonated activated carbon was investigated. Activated carbons were prepared from sugarcane bagasse impregnated with ZnCl2 and NiCl2 solutions, followed by carbonization in a muffle furnace at 550 ºC for 3 hours under a nitrogen atmosphere. Sulfonation was carried out directly with sulfuric acid (98%), using a liquid ratio of 1:10 under reflux at 160 °C for 2 hours for the CA/NiCl2 catalyst and at 217 °C for 4 hours for the CA/ZnCl2 catalyst. The catalysts were characterized by nitrogen adsorption techniques (B.E.T), Raman spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy ( EDS), elemental analysis and ion exchange capacity. The results demonstrated the obtaining of activated carbon with a high surface area (1,100 m2. g-1), and after the sulfonation process, the CA-S/NiCl2 catalyst presented the highest concentration of sulfonic groups inserted in the carbon matrix. The dehydration reactions of cellobiose and glucose to obtain 5-HMF were optimized considering the reaction time of 60, 120 and 180 hours, and temperature of 140°C, 160°C and 180°C as variables. The CA-S/ZnCl2 catalyst demonstrated superior yield and selectivity (70.69% and 72.87%, respectively) compared to different acid catalysts reported in the literature. Finally, it is highlighted that the acid catalysts developed in this study appear as promising alternatives for application in several environmentally safer catalytic routes, aiming to obtain chemical products with high added value as substitutes for those derived from fossil fuels.